2022
DOI: 10.1155/2022/7905727
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Sepsis in a Resource-Limited Setting: Causative Microorganisms and Antimicrobial Susceptibility Profile

Abstract: Background. Empiric treatment of suspected neonatal sepsis must be based on data on setting-specific causative pathogens and their respective susceptibilities to antimicrobials, as well as universal treatment guidelines. This approach will ensure better therapeutic outcomes and reduce mortality. Objectives. The objectives of this study were to determine the bacteriological profile and antibiotic susceptibility pattern of isolated microorganisms responsible for neonatal sepsis in a regional hospital in Ghana. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Our report showed that gram-negative bacteria were the predominant isolated organisms (79.8%) causing neonatal sepsis which was congruent with studies reported from Ethiopia 30% (33) Nigeria78.9% (30), Madagascar 81% (53) and Nepal 69.6% (54). On the contrary, studies in Ethiopia and other countries reported that gram positive bacteria were common cause of neonatal sepsis (23,49), Ghana (31), China (55) and Iran (56).…”
Section: Discussionsupporting
confidence: 89%
“…Our report showed that gram-negative bacteria were the predominant isolated organisms (79.8%) causing neonatal sepsis which was congruent with studies reported from Ethiopia 30% (33) Nigeria78.9% (30), Madagascar 81% (53) and Nepal 69.6% (54). On the contrary, studies in Ethiopia and other countries reported that gram positive bacteria were common cause of neonatal sepsis (23,49), Ghana (31), China (55) and Iran (56).…”
Section: Discussionsupporting
confidence: 89%
“…2 In addition, grampositive microorganisms are far more prevalent than gram-negative organisms in LOS observed in NICUs. 13 However, we found that the causative microorganism for LOS did not predict COHb elevation.…”
Section: Statistical Analysis "Ibm Spss Statistics Formentioning
confidence: 62%